CULTURAS CROMOGÊNICAS ISOLADAS DE LEPROMAS MURINO E HUMANO - Gomes, J. M.; Souza, Lindolfo A. de (Arquivos da Faculdade de Higiene e Saúde Pública da Universidade de São Paulo, 1949)
The AA. reports the results they obtained after more than lO years of research, during which, starting from murine and human lepromas, he succeeded in isolating, many times, always the same type of chr.omogeDic cultures of alcohol-acid fast bacilli. Culture media used were: 5% glycerinated gelose, Petragnani and 5% glicerinated broth. The first cultures obtained differed entirely from the known and accepted aspect of cultures of acid fast bacteria. They were smooth, moist, of an ochre or salmon color; the organisms showed a great polymorphisn• and in the great majority were acid sensitive. In the course of his studies the AA. made -a point of not ignoring any of his findings; finaliy succeeding to obtain typical chromogenic cultures formed exclusively of acid fast cocco-bacilli. The micro-organism appeared in the artificial culture media under twu distinct aspects: lst.) smooth, moist, ochre or salmon color cultmes; 2nd.) following the first type, yellow, dry and granulated cultures appear. In the course o f his long period of observation, three f actors seemed of the utmost importance to the AA.: lst.) aging o f the leproma, which was kept sterile in the refrigerator, sealed in paraffin; 2nd.) drying of a wire loop taken from a mooth culture, diluting it later in distilled water and thus incubated for 24 or 8 hours and then plantcd in Petragnani's medium. By mean of these methods of "violence", comparable to those used for obtaining a,;.a from certain fungi, a great number of organs are formcd, which the AA. name '·fungiform bodies", that are intensively acid fast, full of corpuscles or even bacilii. that are projected around the membrane.This process lf rnultiplieation thus increases the numher of acid fast haeilli. 3rd) The length of time during which Lhe organisms are kept in the same culture medium is ;mportant; once its nutritive properties are exhausted, the acid sensitive organisms die, remaining only those of greater capacity of adaptation, the acid fast hacilli. This process of natural selection takes several months -- from 4 to 7, counting from the first seeding.The next AA. demonstrate that the "globias" of Marchoux -- which must he differentiated from the "globis" of Neisser - are the same "fungiform bodies" found in the cultures. In the smooth colonies, formed mostly of acid sensitive organism, this method o f multiplication is natural; however, i f one wishe:, to force its tramsformation into arid fast organisms, one has to submit the culture to "violence" and starvation, in order that, seeding them in a more nutritive medium, "fungiform bodies" will be formed.Its multiplication depends, therefore, of ''suffering", followed by facilities offered by the more nutritive medium.In the human or animal body it is found in the phase of the leprotic state,in which absolute tolerance to parasiti:im is observed (a situation similar to that noted in Pedragnani´s medium), i.e., an anergic condition. In the first phase. struggling to adapt themselves to the environmental conditions, the organisms are scattered (multiplication at this phase hy fission); in the last phase. fighting the specific anti-bodies, the organisms are also found scattered and only occasionally they regress to the form of globias, under the influence of other infections or hypo-nutritive conditions.The AA. admit that the M. of Hansen and the M. of Stefansky have a long cyclogenic life ("Revista Brasileira de Medicina'', August 1910) and distinguishes two phases of the M. as parasites: first evolutive which the AA. admit Lhe following forms: infra-microbic, homogeneous acid fast bacillus, granulated acid fast bacillus, acid fast granulations and acid last dusts; 2nd. - involutive phase: the following forms are observed in this phase: infra-microbic, homogeneous acid fast bacillus, fragmented acid fast bacillus, acid sensitive bacillus, acid sensitivc granulations ..... destruction. SuIfo na treatment; throught out other types o f involution: Large acid fast or sensitive granulations, even larger, than a Staphilococcus; large acid sensitive bacillus. curved, vacuolated, claviform, etc. As to the dark granulations which appear in the course of the infection or treatment, contrary to many investigators, the AA. believe that they are forms of resistance. Studying the morphology of the organisms in the culture media, the AA. describe the following forms: a - acid fast bacilli, grown on débeis of human or animal tissues; b - large or small acid sensitive bacilli;c - acid sensitive "fungiform bodies"; d  - acid sensitive corpuscles; some are acid fator with acid fast nucleus; e - acid sensitive bacilli. thin and short; acid fast bacilli in small numher; same acid sensitive corpuscles and acid fast in the geat majority with acid fast nucleus. And now the cullture. moist. pasty. al a stand still, without the aspect of the cultures of acid fast bacteria. They are then submited to dessication. The following is then observed: f - a great number of acid fast ''fungiform bodies";g  - acid fast corpuscles and bacilli.mixed with acid sensitive corpuscles and bacilli; a new stand still is noticed. If one insists on des· icating the culture, its stabilization will be hastened; however, it is the length of time - 4,5,6,7 months -- that is decisive. During that period of time culture medium is nearly completely dried out. All the acid sensitive organisms die. The material is now planted in Petragnani's. The following is observed: h - finally. dry and granulated colonies appear, forrned exclusively by a.r. coccobacilli; Petragnani´s medium wiyh malachite green which formerly becarne colorless, now keeps its color. The culture now is stabilized and presents the typical aspect ( dry and granulated) of the colonies of other acid fast bacteria. Conservation of smooth colonies for severa! months in 5%i glycerinated broth gives the sarne results as the aging of the solid medium because the toxic substances elaborated by the micro-organism finally render it for vegetation and only the resistant forrns ( dark granulations) survive.